Cytotaxonomy of the subgenus Artibeus (Phyllostomidae, Chiroptera) by characterization of species-specific markers - Marcela de Lemos Pinto; Merilane da Silva Calixto; Maria José de Souza; Ana Paloma Tavares de Araújo; Alfredo Langguth; Neide Santos (Comparative Cytogenetics, 2012)
The genus Artibeus represents a highly diverse group of bats from the Neotropical region, with four large species occurring in Brazil. In this paper, a comparative cytogenetic study was carried out on the species Artibeus obscurus Schinz, 1821, A. fimbriatus Gray, 1838, A. lituratus Olfers, 1818 and A. planirostris Spix, 1823 that live sympatrically in the northeast of Brazil, through C-banding, silver staining and DNA-specific fluorochromes (CMA3 and DAPI). All the species had karyotypes with 2n=30,XX and 2n=31,XY1Y2, and FN=56. C-banding showed constitutive heterochromatin (CH) blocks in the pericentromeric regions of all the chromosomes and small CH blocks at the terminal region of pairs 5, 6, and 7 for all species. Notably, our C-banding data revealed species-specific autosomic CH blocks for each taxon, as well as different heterochromatic constitution of Y2 chromosomes of A. planirostris. Ag-NORs were observed in the short arms of chromosomes 5, 6 and 7 in all species. The sequential staining AgNO3/CMA3/DA/DAPI indicated a positive association of CH with Ag-NORs and positive CMA3 signals, thus reflecting GC-richness in these regions in A. obscurus and A. fimbriatus. In this work it was possible to identify interespecific divergences in the Brazilian large Artibeus species using C-banding it was possible provided a suitable tool in the cytotaxonomic differentiation of this genus.